Cancer-Cell-Intrinsic cGAS Expression Mediates Tumor Immunogenicity - Schadt, Linda; Sparano, Colin; Schweiger, Nicole Angelika; Silina, Karina; Cecconi, Virginia; Lucchiari, Giulia; Yagita, Hideo; Guggisberg, Emilien; Saba, Sascha; Nascakova, Zuzana; Barchet, Winfried; van den Broek, Maries (Cell reports, 2019)
Sensing of cytoplasmic DNA by cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) synthase (cGAS) results in production of the dinucleotide cGAMP and consecutive activation of stimulator of interferon genes (STING) followed by production of type I interferon (IFN). Although cancer cells contain supra-normal concentrations of cytoplasmic DNA, they rarely produce type I IFN spontaneously. This suggests that defects in the DNA-sensing pathway may serve as an immune escape mechanism. We find that cancer cells produce cGAMP that is transferred via gap junctions to tumor-associated dendritic cells (DCs) and macrophages, which respond by producing type I IFN in situ. Cancer-cell-intrinsic expression of cGAS, but not STING, promotes infiltration by effector CD8+ T cells and consequently results in prolonged survival. Furthermore, cGAS-expressing cancers respond better to genotoxic treatments and immunotherapy. Thus, cancer-cell-derived cGAMP is crucial to protective anti-tumor CD8+ T cell immunity. Consequently, cancer-cell-intrinsic expression of cGAS determines tumor immunogenicity and makes tumors hot. These findings are relevant for genotoxic and immune therapies for cancer.
Keywords: Membrane Proteins; Humans; nukleotidy cyklické; Disease Progression; dendritické buňky; Microsatellite Repeats; cancer; lidé; Immunotherapy; zvířata; Interferon Type I; myši inbrední C57BL; CD8-Positive T-Lymphocytes; CD8-pozitivní T-lymfocyty; Nucleotides, Cyclic; CD8(+) T cells; nukleotidyltransferasy; cGAMP; interferon typ I; cGAS; immunotherapy; Dendritic Cells; Mice, Inbred C57BL; Neoplasms; STING; nádorové buněčné linie; nádory; mikrosatelitní repetice; poškození DNA; membránové proteiny; DNA Damage; chemotherapy; progrese nemoci; gap junctions; Animals; Cell Line, Tumor; Nucleotidyltransferases; imunoterapie; type I IFN; radiotherapy